An islamic perspective on the inclusion of learners with disabilities in private mainstream education in Dubai: interpretations and implications - Alibhai, Zamena Hassan (2010)
As the United Arab Emirates (UAE) undertakes this tremendous journey of adopting inclusive ideologies from the west, this study aims to ascertain if the Islamic teachings coincide with inclusive practices and if they will enhance the situation of learners with disabilities in Dubai, UAE. This qualitative study analyzes the juxtaposition of secular and Islamic ideologies in the framework of this Islamic State. In analyzing the interpretations of Islamic views on disabilities, references to relevant scholarly literature, interpretations from stakeholders and real life implications of ‘inclusive practices’ in Dubai, this research study presents an Islamic perspective on the inclusion of learners with disabilities in private mainstream education. Management, teachers and parents were interviewed for their interpretations of the Islamic perspectives on the inclusion of learners with disabilities. Observations were conducted to assess inclusive practices of a mainstream school employing early intervention practices. The findings of this study revealed that Islamic teachings and the ideal of inclusion in literature seemed to be in harmony although implementation remains a tangible ideal. Recommendations for further practice and research are provided to bring to fruition this valuable amalgamation of ideologies in the UAE.